The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0253475
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload inhibits BMP/SMAD and IL-6/STAT3 signaling to hepcidin in cultured hepatocytes

Abstract: Hepcidin is a peptide hormone that targets the iron exporter ferroportin, thereby limiting iron entry into the bloodstream. It is generated in hepatocytes mainly in response to increased body iron stores or inflammatory cues. Iron stimulates expression of bone morphogenetic protein 6 (BMP6) from liver sinusoidal endothelial cells, which in turn binds to BMP receptors on hepatocytes and induces the SMAD signaling cascade for transcriptional activation of the hepcidin-encoding HAMP mRNA. SMAD signaling is also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…While experimental iron loading of cultured cells is rapid, dietary iron loading of mice is gradual (20) and most of excess iron is effectively detoxified within ferritin, which is highly induced (30). By contrast, the suppression of hepcidin preceded ferritin induction in cultured cells (10), which may explain the discrepancy with the in vivo data.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…While experimental iron loading of cultured cells is rapid, dietary iron loading of mice is gradual (20) and most of excess iron is effectively detoxified within ferritin, which is highly induced (30). By contrast, the suppression of hepcidin preceded ferritin induction in cultured cells (10), which may explain the discrepancy with the in vivo data.…”
Section: Discussionmentioning
confidence: 92%
“…We sought to analyze how iron overload affects hepcidin-mediated inflammatory responses. We and others reported that excess iron inhibits the major hepcidin signaling pathways (BMP/SMAD and IL-6/STAT3) in cultured cells (10,11). To explore the physiological relevance of these findings, wt mice were subjected to variable degrees of dietary iron loading and then treated with LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variation at TMPRSS6 is also associated with biomarkers of iron overload 53 . SMAD7 (rs72917789, SBP p = 1.14x10 − 8 ) has been shown to modulate expression of hepcidin, a key regulator of intestinal iron absorption 54,55 . Additionally, GSMT1 (rs36209093, DBP p = 9.94x10 − 15 ), encoding glutathione S-transferase Mu 1, has been implicated in cardiomyopathy due to iron overload 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, activated NFE2-related factor 2, by sensing systemic iron accumulation or by treatment with EGCG, can induce BMP-6 and hepcidin expression by binding to the antioxidant response element on the gene promoter, subsequently decreasing serum iron levels and iron toxicity [51,52]. Interestingly, it is reported that hepatocellular iron accumulation inhibited hepcidin expression by suppressing BMP/SMAD and IL-6/STAT3 signaling [53]. Our previous findings have shown that EGCG at a high concentration can diminish IL-6-induced hepcidin expression and secretion through the induction of FOXO1-dependent SMILE expression, which, in turn, can increase serum iron levels [20].…”
Section: Discussionmentioning
confidence: 99%